RELATIONSHIP BETWEEN WORK MOTIVATION AND WORK ENVIRONMENT WITH WORK DISCIPLINE OF STATE FIRST MIDDLE SCHOOL TEACHER - Nurlailah NURLAILAH (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2022)
The aims of the study were to determine: 1) The relationship between work motivation and teacher work discipline, 2) the relationship between the work environment and teacher work discipline, 3) the relationship between work motivation and work environment together with the work discipline of junior high school teachers in the state junior high schools in Indonesia. Palmerah District, West Jakarta. This research was conducted using a survey method. The affordable population was 134 teachers and the research sample was taken by 100 public junior high school teachers in Palmerah District, West Jakarta. To obtain the validity of the questionnaire items, the product moment correlation was used with the results: from 33 items of Teacher Work Discipline, 30 items were declared valid; of 34 items of Work Motivation, 31 items are declared valid; and from 36 items of Work Environment, 34 items are declared valid.